ETNOGRAFI 5 PEREMPUAN PENYAPU JALAN (Study Kasus di Kecamatan Pontianak Tenggara Kota Pontianak Kalimantan Barat) - LYUDMITA KAROLINA MARITO BAKARA (Universitas Tanjungpura, 2021)
AbstractThe street sweeper profession is always described as a world of work for men. The street sweeper workers have a high risk. Currently the street sweeper profession is not only done by men, but also women. Women as street sweepers can be found in almost all parts of Indonesia. The Street Sweeper is a natural and common thing. The research is a case study which focuses on 5 street sweeper women in Kecamatan Pontianak Tenggara, Kota Pontianak, Kalimantan Barat. Working as a street sweeper is a source of income that can help the household economy to fulfil primary, secondary and tertiary needs. The formulation of the research problem is